Pemasangan Radar Pantai Guna Identifikasi Potensi Ancaman di Laut Wilayah Selatan Pulau Jawa - Provid Ariantoko; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno; Endro Legowo; Moch Yurianto (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract This paper discusses the conditions of vulnerability and potential threats to security in the marine area of ​​the southern part of Java Island and the level of capability of the elements operating in the area whose conditions are still inadequate both in quality and quantity. This thesis uses qualitative research methods. The author has a plan to conceptualize the installation of coastal radar to increase security in the area. The author uses the IMSS (Integrated Maritime Surveillance System) radar which is already operating in the Malacca Strait area as an empirical example and will develop the concept of coastal radar in the southern region of Java Island. With coastal radar in the area that functions as an early warning system, it is hoped that all forms of threats and violations can be anticipated very well. Keywords: Coastal radar, IMSS, Potential threats.